A Comparative Analysis of Character Education in Low-Grade Students in China and Indonesia - Rosfaniarti Rosfaniarti (Edumaspul: Jurnal Pendidikan, 2024)
This article discusses Character Education in Two Countries with different cultural backgrounds, conditions and ideologies, namely China and Indonesia. For this reason, this analysis was made as a comparison of the implementation of character education in China and Indonesia with the aim that it can later be applied in character education planning that can be applied in schools. This analysis uses qualitative literature techniques, where information is collected from various cultural education journals and other sources related to the topic of discussion. The analysis found that two countries place character education as the main pillar in forming the education curriculum. However, there are differences in curriculum content, character interpretation, and implementation methods. China implements character education with Di Zi Gui literacy, which strengthens morals and character. And Indonesia implements character education through the values ​​of the Pancasila Student Profile Strengthening Project.